PENINGKATAN KUALITAS HUKUM KAMPUNG MELALUI PELATIHAN DAN PEDAMPINGAN DI KAMPUNG ONGGAYA, DISTRIK NAUKENJERAI, KABUPATEN MERAUKE - Mulyadi Alrianto Tajuddin; Marlyn Jane Alputila; Nur Jalal (Musamus University, 2019)
Regulations in the onggaya village sometimes do not pay attention to the needs or conditions of the village according to the level of the draft legislation. Training and assistance improve the ability to formulate village regulations or other legal products as well as experience in the field of government also greatly affect the ability and technical skills with their area of ​​work. The method used is socialization activities, training and technical guidance for the preparation of village regulation making techniques through socialization and training activities including the development of lecture training materials from speakers, case studies, group discussions, games and brainstorming carried out in three stages, namely socialization, training and technical guidance as well as assistance in drafting village regulations in onggaya, for 8 months in 2019. Targets of this activity: (1) Equipping the Onggaya Village Deliberation Board and the Onggaya Village Chief with basic legal knowledge regarding the techniques for drafting village regulations. (2) Providing skills in making arrangements related to village regulation making. (3) Form a networking between the team and partners in this case the Onggaya Village Deliberation Board and the Onggaya Village Chief to assist in the formulation of village regulations.